Tinjauan Kriminologis terhadap Pelaku Kejahatan Ekonomi: Studi Kasus Pengoplosan Pupuk di Kalianda, Lampung Selatan - Muhammad Akhdan Mizanulhaq; Firganefi Firganefi; Fristia Berdian Tamza (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study examines the crime of fertilizer counterfeiting in the Kalianda area, South Lampung, which is a form of economic crime with a significant impact on the agricultural sector. Fertilizer counterfeiting not only harms farmers financially, but also disrupts the distribution of subsidized fertilizers and lowers trust in the legal system. This crime is driven by various factors, including economic incentives, weak supervision, and inadequate regulations. In addition, the existence of illegal distribution networks and the lack of effectiveness of law enforcement also exacerbate the problem. This study uses a normative juridical approach to analyze the legal aspects that govern the crime of fertilizer counterfeiting, as well as an empirical approach through interviews with law enforcement officials in the South Lampung Regional Police area. The results of the study show that the rampant counterfeiting of fertilizers is caused by economic pressure, weak law enforcement, and low public legal awareness. This practice is often carried out in a covert manner and is difficult to prove technically in the field. In addition, the alleged involvement of certain individuals in the illegal distribution network adds to the complexity of handling cases. This study recommends reforming the fertilizer distribution system that is more transparent, increasing supervision by law enforcement officials and related agencies, and strengthening regulations with the application of stricter sanctions. Efforts to increase public legal awareness are also an important aspect in preventing similar crimes in the future. In addition, the need for synergy between law enforcement officials, local governments, and the community is the main key in tackling this economic crime. The development of fertilizer distribution tracking technology, as well as education to farmers about the characteristics of real and fake fertilizers, is expected to be able to strengthen the protection system at the grassroots level.